Strategi Manajemen Pemasaran Unggul Jasa Pendidikan di SMP Islam Terpadu Ar Ruhul Jadid Jombang - Beny Sintasari; Nailatul Afifah (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2022)
The purpose of this article is to describe a superior marketing management strategy because competition in the field of education is getting tougher. This type of research uses qualitative methods. Data collection techniques using interviews, observation, and documentation. Instruments in the form of a list of questions and observation sheets. The data analysis technique uses data reduction, coding, and drawing conclusions. The results of this study indicate that a superior marketing management strategy is evidenced by careful planning, implementation of a structured program in accordance with organizational performance that is competent, and supervision that is more directed towards institutional improvement. This educational institution has a good and quality image in the eyes of the community, it will have a great opportunity to acquire students. Arrruhul Jadid Islamic Junior High School has a strategy for implementing the marketing of educational services both online and offline, this strategy helps achieve the goals of the school institution and supports the implementation of the school's mission. That this superior strategy contributes to Islamic institutions’ order to develop following the rapid world of education.